Can the Antimicrobial Peptide Ctx(Ile21)-Ha-Ahx-Cys Grafted onto Nanochitosan Sensitize Extensively Drug-Resistant Mycobacterium tuberculosis? - Laura Maria Duran Gleriani Primo; Cesar Augusto Roque-Borda; Eduardo Festozo Vicente; Paula Aboud Barbugli; Fernando Rogério Pavan (Chemistry Proceedings, 2022)
The infectious agent Mycobacterium tuberculosis (MTB) has several defense and resistance mechanisms that must be eliminated. The treatment is prolonged, which in many cases generates susceptibility to microbial resistance. This research aimed to study whether the antimicrobial peptide Ctx(Ile21)-Ha-Ahx-Cys (Ctx-SH) functionalized in nanochitosan matrices could eliminate resistant MTB. For this, a nanosystem was developed with chitosan matrices previously modified with N-acetylcysteine functionalized to Ctx-SH. Modified chitosan nanoparticles (NPQ) were obtained by ionic gelation using sodium tripolyphosphate and loaded with rifampicin. Both chitosan and NPQ modifications were analyzed for physicochemical parameters by Fourier/Raman transform infrared spectroscopy and Zeta potential. Antimicrobial activity was performed in a level 3 biosafety laboratory with strains H37Rv (standard) and CF169 (extensively drug-resistant, XDR) incubated in 7H9 broth supplemented with oleic acid, albumin, dextrose, and catalase at 37 °C and 5% CO2 and read using fluorescence with 0.01% resazurin after 7 days. Insertion and mapping of NPQ into macrophages were assessed using a confocal microscope after 24 h with NPQ conjugated to fluorescein isothiocyanate. Preliminary results show that the spectroscopies corroborate the hypothesis of the functionalization of the Ctx-SH peptide to the chitosan-N-acetylcysteine system because, when comparing the three spectroscopies, a gradual increase in the intensity of several bands and the formation of captive disulfide are observed, and the Zeta potential (+30 mV) confirmed high application stability. Bacterial inhibition studies revealed that rifampicin-loaded antimicrobial peptide-conjugated chitosan nanoparticles have better activity than rifampicin alone against CF169, with a minimum inhibitory concentration of <0.977 µg/mL, similar to the standard strain. In addition, it was shown that NPQ would be able to enter the macrophage without causing toxicity and thus take better advantage of the activity of rifampicin. Finally, it is possible to verify that the nanobioconjugation of the Ctx-SH-N-acetylcysteine-chitosan compound is capable of enhancing the activity of obsolete drugs and/or sensitizing XDR bacteria.